Adolescent Smoking Susceptibility: Gender-Stratified Racial and Ethnic Differences, 1999–2018 - Kamke, Kristyn (Am J Prev Med, 2020)
INTRODUCTION: Susceptibility, or openness to smoking, is a predictor of future smoking. This study examines within-gender racial/ethnic differences in smoking susceptibility over historical time (1999–2018) and developmental age (11–18 years). METHODS: Data were from 205,056 adolescent never smokers in 14 waves of the National Youth Tobacco Survey. Weighted time-varying effect models were used to estimate nonlinear trends in smoking susceptibility among minority (versus white) adolescents. Analyses were conducted in 2019. RESULTS: Compared with whites, Latino/a adolescents were consistently more susceptible to smoking, whereas black and Asian adolescents fluctuated between being less and equally susceptible over time. American Indian, Alaska Native, Native Hawaiian, and Pacific Islander adolescents were more susceptible from 2014 to 2017, with differences being larger for girls. Susceptibility peaked at age 14 years. Compared with whites, Latino/a adolescents were more susceptible throughout adolescence. Black adolescents were more susceptible in early adolescence, whereas Asian adolescents were less or equally susceptible to smoking in early to mid-adolescence. American Indian, Alaska Native, Native Hawaiian, and Pacific Islander girls were more susceptible in early and mid-adolescence, but boys were more susceptible in early adolescence only. American Indian, Alaska Native, Native Hawaiian, and Pacific Islander girls were less susceptible than white girls at age 18 years. CONCLUSIONS: Twenty-year racial/ethnic differences in smoking susceptibility were evident, particularly among girls, but were mostly equivalent between genders over developmental age. Targeting susceptible adolescents with gender-, race/ethnic-, and age-tailored prevention efforts may prevent or delay adolescents’ transition to tobacco use and reduce tobacco-related disparities.